OPTIMASI RUTE TERPENDEK JALUR DISTRIBUSI OBAT-OBATAN DENGAN METODE TRAVELING SALESMAN PROBLEM ALGORITMA TABU SEARCH - Devani, Vera; Sari, Atika Muthia (Program Studi Teknik Industri, Fakultas Teknik Universitas Tarumanagara, 2025)
The company processes the distribution of medicines using the FIFO (First In First Out) system. This can enable the distribution route for medicines to be longer because delivery is based on an order list. Traveling Salesman Problem Method The Tabu Search algorithm is a method that can be used to solve distribution problems, by evaluating each iteration until the optimal route is found. To find out the distribution route for medicines with the shortest distance and time. The results of this research show that the optimal distribution route for this company is 23.3 km and the travel time is 55 minutes on the route from Distributor - PT. Awal Bros Putra Medika – Tabrani Hospital – PT. Ekamas International Hospital – Awal Bros A. Yani Hospital - ASEAN Pharmacy. Meanwhile, based on real conditions, the salesman's distribution route covers a distance of 23.9 km and a travel time of 63 minutes on the route from Distributor - PT. Awal Bros Putra Medika – Tabrani Hospital – PT. Ekamas International Hospital – Awal Bros A. Yani Hospital - ASEAN Pharmacy. From the two distribution routes, it was found that the difference in travel distance was 0.6 km and travel time was 8 minutes.